Method for extracting cellulose nanocrystals from passion fruit peel waste
Through the method of extracting cellulose nanocrystals from passion fruit peels, including pretreatment, removal of impurities and sulfuric acid hydrolysis, the problem of low extraction efficiency of cellulose nanocrystals in passion fruit peels is solved, and high yield and high purity cellulose nanocrystal preparation is achieved, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202510081235.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
How to extract cellulose nanocrystals that meet the needs of use from passion fruit peels and make full use of useful compounds for passion fruit peels.
Cellulose nanocrystals are extracted from passion fruit peels through a series of steps, including pretreatment, removal of water-soluble substances and impurities, sulfuric acid hydrolysis, condensation water treatment, dialysis-centrifuge-freeze-drying treatment, and cellulose nanocrystals with high yield, purity and crystallinity.
It has achieved efficient extraction of cellulose nanocrystals from passion peel waste, with a yield of 36.27%±0.18%. It has the advantages of nanostructure, high aspect ratio, high purity, and high crystallinity. It is suitable for enhancing composite material performance and nanomaterial modification and synthesis.
Smart Images

Figure CN119874945A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cellulose nanocrystal preparation, and in particular to a method for extracting cellulose nanocrystals from passion fruit peel waste. Background Art
[0002] Passion fruit is grown all over the world, especially in the pan-tropical regions of America, where the yield is high and the variety is diverse. Although passion fruit pulp is highly commercialized, few studies have focused on the utilization of by-products such as passion fruit peel. Studies have shown that passion fruit peel accounts for 50% to 60% of the total weight of the fruit and contains many useful compounds, such as cellulose, pectin, biochar, and phenolic compounds.
[0003] After acid hydrolysis, the amorphous regions in cellulose can be removed, thus forming cellulose nanocrystals (CNCs) with a rod-like structure of nanometer size and high crystallinity. CNCs have excellent physical and chemical properties, such as high surface-to-volume ratio, high mechanical strength, easy surface modification, biodegradability and biocompatibility, which makes them have very broad application prospects in drug delivery, enhancing the performance of composite materials, improving the stability of Pickering emulsions, and synthesizing nanomaterials.
[0004] Based on the above content, how to extract cellulose nanocrystals that meet usage requirements from passion fruit peel is a problem that needs to be solved urgently. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for extracting cellulose nanocrystals from passion fruit peel waste, which solves the problems mentioned in the background technology.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] A method for extracting cellulose nanocrystals from passion fruit peel waste comprises the following steps:
[0008] S1. Obtaining pure cellulose powder:
[0009] S1.1, pre-treating the passion fruit peel without the contents to obtain passion fruit peel powder;
[0010] S1.2, removing water-soluble substances from passion fruit peel powder;
[0011] S1.3, remove impurities in passion fruit peel powder at one time, including lignin and hemicellulose;
[0012] S1.4, removing the impurities in the passion fruit peel powder for a second time to obtain pure cellulose powder;
[0013] S2. Preparation of cellulose nanocrystals:
[0014] S2.1, pure cellulose powder prepared by hydrolyzing S1.4 with sulfuric acid solution;
[0015] S2.2, adding condensed water to the hydrolyzate to remove the residual sulfuric acid in the pure cellulose powder after hydrolysis;
[0016] S2.3. The pure cellulose powder after hydrolysis is subjected to dialysis-centrifugation-freeze drying treatment to obtain cellulose nanocrystals.
[0017] Furthermore, in S2.1, the sulfuric acid concentration of the sulfuric acid solution is 61%, and the ratio of pure cellulose powder added is 1:20 (w / v).
[0018] Furthermore, in S2.1, the hydrolysis temperature of the sulfuric acid solution is 55°C.
[0019] Furthermore, in S2.1, the hydrolysis time is 2 h.
[0020] Furthermore, the specific steps of S1.1 are:
[0021] Take the passion fruit peel with the contents removed, soak it in water, wash it, and then cut it into small pieces;
[0022] Place a small piece of passion fruit peel in a 65°C oven and dry for 48 hours to obtain passion fruit dried peel;
[0023] The passion fruit peel was ground into powder using a grinder and then passed through a 100-mesh sieve to obtain passion fruit peel powder.
[0024] Furthermore, the specific steps of S1.2 are:
[0025] Heat the passion fruit peel powder in 80°C water at a ratio of 1:20 (w / v) to remove water-soluble substances in the passion fruit peel powder;
[0026] After heating, the passion fruit peel powder is filtered and dried at 65°C.
[0027] Furthermore, the specific steps of S1.3 are:
[0028] The dried fragrant fruit peel powder was mixed with 10% (w / v) sodium hydroxide solution in a ratio of 1:10 (w / v), and placed in a water bath at 80°C for 4 hours to remove impurities in the fragrant fruit peel powder at one time;
[0029] The fragrant fruit peel powder is filtered and washed 4-5 times and then dried at 65°C.
[0030] Furthermore, the specific steps of S1.4 are:
[0031] The fragrant fruit peel powder was mixed with 7.5% (w / v) sodium chlorite solution in a ratio of 1:10 (w / v), and placed in a water bath at 75°C for 3 hours to perform secondary impurity removal;
[0032] Filter and wash the fragrant fruit peel powder to a neutral pH value, and dry it at 65°C to obtain pure cellulose powder.
[0033] Furthermore, the specific steps of S2.2 are: adding 10 times 4°C condensed water to the hydrolyzate to terminate the reaction, and centrifuging at 4°C and 1000×g for 20 min to remove residual sulfuric acid in the pure cellulose powder after hydrolysis.
[0034] Furthermore, the specific steps of S2.3 are:
[0035] The pure cellulose powder after hydrolysis is placed in a 6000-8000Da dialysis bag for 3 days to remove the remaining small molecular impurities in the pure cellulose powder after hydrolysis;
[0036] Collect the liquid in the dialysis bag and centrifuge it again at 4°C, 1000×g for 15 min to obtain the supernatant;
[0037] The supernatant was freeze-dried for 48 h to obtain cellulose nanocrystals.
[0038] The present invention provides a method for extracting cellulose nanocrystals from passion fruit peel waste. Compared with the prior art, the method has the following beneficial effects:
[0039] 1. The sulfuric acid concentration, hydrolysis temperature and hydrolysis time conditions with the highest yield are given, and the highest yield can be 36.27%±0.18%;
[0040] 2. The peel of fragrant fruit is a good source of cellulose and can be used as a raw material for the production of CNC. It has the advantages of nanostructure, high aspect ratio, high purity, and high crystallinity, which is conducive to playing an important role in enhancing the performance of composite materials and nanomaterial modification and synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 A schematic flow chart of a method for extracting cellulose nanocrystals from passion fruit peel waste of the present invention is shown;
[0043] Figure 2 A schematic diagram showing the effect of sulfuric acid concentration on CNC yield of the present invention is shown;
[0044] Figure 3 A schematic diagram showing the effect of the hydrolysis temperature on the CNC yield of the present invention is shown;
[0045] Figure 4 A schematic diagram showing the effect of the hydrolysis time on the CNC yield of the present invention is shown;
[0046] Figure 5 A schematic diagram of a CNC transmission electron microscope of the present invention is shown;
[0047] Figure 6 The schematic diagram of the average diameter and diameter distribution of CNC of the present invention is shown;
[0048] Figure 7 The schematic diagram of the average length and length distribution of CNC of the present invention is shown;
[0049] Figure 8 The FTIR spectrum schematic diagram of PP, PPC and CNC of the present invention is shown;
[0050] Fig. 9 The schematic diagram of XRD spectrum of PP, PPC and CNC of the present invention is shown;
[0051] Fig.10 TG curve schematic diagram of PP, PPC and CNC of the present invention is shown;
[0052] Fig.11 A schematic diagram of the DTG curves of PP, PPC and CNC of the present invention is shown. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] In order to solve the technical problems in the background technology, a method for extracting cellulose nanocrystals from passion fruit peel waste is provided as follows:
[0055] Combination Figure 1 As shown, the present invention provides a method for extracting cellulose nanocrystals from passion fruit peel waste, comprising the following steps:
[0056] S1. Obtaining pure cellulose powder:
[0057] S1.1, pre-treating the passion fruit peel without the contents to obtain passion fruit peel powder;
[0058] S1.2, removing water-soluble substances from passion fruit peel powder;
[0059] S1.3, remove impurities in passion fruit peel powder at one time, including lignin and hemicellulose;
[0060] S1.4, removing the impurities in the passion fruit peel powder for a second time to obtain pure cellulose powder;
[0061] S2. Preparation of cellulose nanocrystals:
[0062] S2.1, hydrolyzing the pure cellulose powder prepared in S1.4 with a sulfuric acid solution; the sulfuric acid concentration of the sulfuric acid solution is 61%, and the ratio of the pure cellulose powder is 1:20 (w / v); the hydrolysis temperature is 55°C; and the hydrolysis time is 2h;
[0063] S2.2, adding condensed water to the hydrolyzate to remove the residual sulfuric acid in the pure cellulose powder after hydrolysis;
[0064] S2.3. The pure cellulose powder after hydrolysis is subjected to dialysis-centrifugation-freeze drying treatment to obtain cellulose nanocrystals.
[0065] As an embodiment: the specific steps of S1.1 are: take the passion fruit peel with the contents removed, soak it in water to wash, and then cut it into small pieces; place the small pieces of passion fruit peel in a 65°C oven and dry them for 48 hours to obtain dried passion fruit peel; grind the dried passion fruit peel with a grinder and pass it through a 100-mesh sieve to obtain passion fruit peel powder.
[0066] As an embodiment: the specific steps of S1.2 are: putting the passion fruit peel powder into 80°C water in a ratio of 1:20 (w / v) and heating it to remove the water-soluble substances in the passion fruit peel powder; after heating, filtering the passion fruit peel powder and drying it at 65°C.
[0067] As an embodiment: the specific steps of S1.3 are: mixing the dried fragrant fruit peel powder with 10% (w / v) sodium hydroxide solution in a ratio of 1:10 (w / v), and bathing in 80°C water for 4 hours to remove impurities in the fragrant fruit peel powder at one time; filtering and washing the fragrant fruit peel powder 4-5 times and then drying it at 65°C.
[0068] As an example: the specific steps of S1.4 are: the fragrant fruit peel powder is mixed with 7.5% (w / v) sodium chlorite solution in a ratio of 1:10 (w / v), the solution is adjusted to pH 4.5 with glacial acetic acid, and the solution is water bathed at 75°C for 3 hours to perform secondary impurity removal; the fragrant fruit peel powder is filtered and washed to a neutral pH value, and dried at 65°C to obtain pure cellulose powder. This step can achieve the effect of bleaching the powder and removing impurities such as residual lignin and hemicellulose.
[0069] As an example: the specific steps of S2.2 are: adding 10 times 4°C condensed water to the hydrolyzate to terminate the reaction, and centrifuging at 4°C and 1000×g for 20 min to remove residual sulfuric acid in the pure cellulose powder after hydrolysis.
[0070] As an example: the specific steps of S2.3 are: the pure cellulose powder after hydrolysis is placed in a 6000-8000Da dialysis bag for 3 days to remove the remaining small molecule impurities in the pure cellulose powder after hydrolysis; the liquid in the dialysis bag is collected and centrifuged again at 4°C, 1000×g for 15 minutes to obtain the supernatant; the supernatant is freeze-dried for 48 hours to obtain cellulose nanocrystals.
[0071] In order to verify that the sulfuric acid concentration of the above sulfuric acid solution is 61%, the hydrolysis temperature is 55°C, and the hydrolysis time is 2h, the following verification test is given:
[0072] Firstly, three parameters of sulfuric acid concentration, hydrolysis temperature and hydrolysis time with higher yield were selected by single factor experiment, and substituted into Orthogonal Design Assistant v3.1. Orthogonal experiment was carried out as shown in Table 1. Finally, the best hydrolysis parameters were selected to experimentally determine the yield and verify the results of orthogonal experiment.
[0073] Table 1 Orthogonal experimental design for optimizing the yield of cellulose nanocrystals prepared by sulfuric acid hydrolysis
[0074]
[0075]
[0076] Characterization of the properties of cellulose nanocrystals:
[0077] Transmission electron microscopy: 10ul of 0.05% (w / v) cellulose nanocrystal water suspension was added to a copper grid for precipitation for 1 min. The supernatant was removed with filter paper and 10ul of uranyl acetate was added for staining for 1 min. The supernatant was removed again. After drying at room temperature, the images were detected using a HT7800 transmission electron microscope (Hitachi, Japan) at 80 kV. The particle size of at least 100 nanocrystals was analyzed using Nano Measurer1.2.
[0078] FTIR spectrum: The dried samples (PP, PPC, cellulose nanocrystals) were mixed and ground with potassium bromide in a ratio of 1:100 (w / w), and the tablets were prepared and analyzed using a Nicolet iS10 FTIR infrared spectrometer (Thermo Fisher Scientific, USA). The spectral acquisition range and resolution were set to 4000-500 cm-1 and 8 cm-1, respectively.
[0079] X-ray diffraction (XRD): The XRD patterns of PP, PPC and cellulose nanocrystals were measured using a SmartLab X-ray diffractometer (Rigaku, Japan) with a scanning angle of 5°-50° and a scanning speed of 2° / min. The crystallinity (CrI%) was calculated using the Segal equation:
[0080] CrI(%)=[(I 002 -I AM ) / I 002 ]×100
[0081] Among them I 002 represents the maximum intensity of (002) diffraction at a 2θ value of about 22°, I AM It is the minimum diffraction intensity at a 2θ value of about 18°.
[0082] Thermogravimetric analysis: TG analysis of PP, PPC and cellulose nanocrystals was performed using a TGA / DSC1 simultaneous thermal analyzer (Mettler Toledo, Swiss) (N2, heating rate 10°C / min).
[0083] Results and Analysis:
[0084] Orthogonal experiment to optimize the hydrolysis conditions of cellulose nanocrystals: Figure 2 , 3 , 4 respectively show the effects of sulfuric acid concentration, hydrolysis temperature, and hydrolysis time on the yield of cellulose nanocrystals.
[0085] Figure 2 With the increase of sulfuric acid concentration, the yield of cellulose nanocrystals showed a trend of first increasing and then decreasing. When the sulfuric acid concentration was 61%, the yield of cellulose nanocrystals could reach a maximum of 33.35%±4.08%. However, if the sulfuric acid concentration was too low (57%) or too high (65%), the yield of cellulose nanocrystals was only 3.25%±1.06% and 1.75%±0.63%, respectively, which was significantly lower than the yield of cellulose nanocrystals at 59%, 61%, and 63% sulfuric acid concentrations (p<0.05). Therefore, three levels of sulfuric acid concentrations of 59%, 61%, and 63% were selected for orthogonal experimental analysis.
[0086] Figure 3 It can be seen that when the hydrolysis temperature is less than 45°C, the yield of cellulose nanocrystals shows a significant upward trend with the increase of hydrolysis temperature (p<0.05), and the yield of cellulose nanocrystals can reach 21.83%±2.86% at 45°C. When the hydrolysis temperature is greater than 45°C, the yield of cellulose nanocrystals does not change significantly (p>0.05), so three levels of hydrolysis temperatures of 45°C, 50°C, and 55°C were selected for orthogonal experimental analysis.
[0087] Figure 4 It can be seen that with the extension of hydrolysis time, the yield of cellulose nanocrystals shows an overall upward trend, but there is no significant difference in the yield of cellulose nanocrystals after the hydrolysis time is extended to 1.5h (p>0.05), so three levels of hydrolysis time of 1.5h, 2.0h and 2.5h were selected for orthogonal experimental analysis.
[0088] In summary, we can get the three-factor three-level orthogonal test table (Table 2) and conduct intuitive analysis. It can be seen that the range size is sulfuric acid concentration> hydrolysis temperature> hydrolysis time, so the sulfuric acid concentration factor has the greatest impact on the yield of cellulose nanocrystals, followed by hydrolysis temperature and hydrolysis time. The three-factor analysis and comparison show that the optimal level of the experiment is A2B3C2, that is, 61% sulfuric acid concentration, 55℃ hydrolysis temperature, and 2h hydrolysis time, but this combination is not in the orthogonal analysis table, so verification analysis is needed.
[0089] After repeated experimental verification, it can be obtained that the yield of cellulose nanocrystals of the above combination is 36.27% ± 0.18%, which is greater than the results of all combinations in the orthogonal experiment, and the experimental verification is successful. Therefore, the optimal experimental conditions for the preparation of cellulose nanocrystals are 61% sulfuric acid concentration, 55°C hydrolysis temperature, and 2h hydrolysis time.
[0090] Table 2 Orthogonal test results and analysis table
[0091]
[0092] In order to verify that the cellulose nanocrystals provided by the present invention can be better applied in practice, the following verification process is provided:
[0093] Morphology and particle size analysis of cellulose nanocrystals (CNC): Figure 5 The appearance of cellulose nanocrystals under a transmission electron microscope is shown. Cellulose nanocrystals present a nanometer-sized rigid rod-like structure with a high aspect ratio. Figure 6 , Figure 7 The diameter and length particle size distribution of cellulose nanocrystals are also shown. The obtained cellulose nanocrystals have uniform particle size and are normally distributed. The measured average diameter is 5.12±1.63nm and the average length is 142.98±24.50nm. The aspect ratio of cellulose nanocrystals is an important quantitative indicator to measure the morphology of cellulose nanocrystals, and is also closely related to the application of cellulose nanocrystals. Although cellulose nanocrystals with low aspect ratio (approximately equal to 1, approximately spherical) can form a denser covering layer at the oil-water interface, cellulose nanocrystals with high aspect ratio are more advantageous in reinforcing composite materials and can enhance the barrier properties and crystallinity of composite fiber membranes.
[0094] FTIR infrared spectrum: such as Figure 8The FTIR spectra of passion fruit peel powder, cellulose powder and CNC are shown. The chemical bonds shown in the spectra are analyzed to determine the effect of chemical treatment on the properties of the samples. Here we mark the peaks that all three samples have. The peaks at 3400 and 2900 cm-1 correspond to the stretching vibrations of OH and CH in cellulose, respectively. As the basic chemical bonds in the cellulose repeating unit, this shows that the basic structure of cellulose in the sample has not been destroyed after chemical treatment. The peaks at 1060 and 896 cm-1 correspond to the stretching vibrations of the CO bond of the glucose ring in cellulose and the β-glycosidic bond between glucose monosaccharides, respectively. Their intensity increases in cellulose powder and CNC, probably because the proportion of pure cellulose increases after lignin is removed. The peak at 1630 cm-1 indicates that OH is bent, probably because OH is bound to water molecules. The peaks at 1735 and 1257 cm-1 represent carboxyl groups, which belong to the acetyl group of hemicellulose or the carboxyl ester bond of lignin. Comparing PP, PPC and CNC in the spectrum, the intensity of these two peaks is significantly reduced, indicating that most of the hemicellulose and lignin in the sample are dissolved and removed after chemical treatment.
[0095] X-ray diffraction: XRD patterns can show the crystal structure of the sample and calculate the crystallinity of the sample to determine the structural changes of the sample after treatment, which is related to the hydrolysis of the amorphous region of CNC. Fig. 9 It can be seen that the three samples all show diffraction peaks near 15.9 degrees, 22 degrees, and 34.7 degrees, which correspond to the (110), (200), and (004) crystal planes of cellulose I, respectively. This shows that after chemical treatments such as cellulose extraction and sulfuric acid hydrolysis, the crystal structure of cellulose I from natural sources remains unchanged. However, among the three samples, the cellulose characteristic peak intensity of PP is the weakest, and the PP crystallinity is only 27.31%. After treatment with sodium hydroxide and sodium chlorite, the crystallinity of PPC is increased to 48.83%. It can be seen that the characteristic peak is not obvious due to the low cellulose content in PP, and the high content of lignin and hemicellulose impurities also makes the initial crystallinity of PP low. After subsequent cellulose purification treatment, the crystallinity of PPC has become higher. After further sulfuric acid hydrolysis treatment, the cellulose characteristic peak intensity of CNC is higher, and the crystallinity has also increased to 64.87%. This also shows that the amorphous region of cellulose is hydrolyzed by sulfuric acid to obtain CNC with higher crystallinity;
[0096] Thermogravimetric analysis: The simultaneous thermal analysis shows the mass changes of the three samples during the heating process, which shows the changes in the thermal stability of the samples after chemical treatment. Fig.10The thermogravimetric analysis curves show that the weight loss rate of all samples below 100°C is less than 10%, which is the evaporation of the remaining bound water on the surface of the dried samples; they all show a large mass loss at around 200-380°C, which is mainly due to the pyrolysis of the main components such as cellulose, hemicellulose, and lignin; in the range of 380-500°C, the weight loss can be attributed to the breakage of glycosidic bonds and the degradation of the molecular carbon skeleton, eventually forming a carbonized residue.
[0097] from Fig.11 From the DTG curve, we can see that due to the different pyrolysis ranges of different components, the pyrolysis of PP containing various impurities such as hemicellulose and lignin has many different stages. However, most of the hemicellulose and lignin in PPC and CNC are removed, and the purity is high, so only one peak appears in the DTG curve. The temperature at which the peak appears is the optimal pyrolysis temperature for achieving the maximum thermal decomposition rate. The optimal pyrolysis temperature of CNC is 293.99℃. However, this temperature is lower than the optimal pyrolysis temperatures of PP (310.31℃) and PPC (340.75℃), indicating that CNC has lower thermal stability, which is mainly because CNC has a larger surface area exposed to high temperatures.
[0098] In summary, cellulose was extracted from passion fruit peel waste and further hydrolyzed into CNC with sulfuric acid. The sulfuric acid concentration, hydrolysis temperature and hydrolysis time conditions that can obtain the highest CNC yield were explored by designing single factor experiments and orthogonal experiments, which were 61% (w / w), 55℃, and 2h, respectively, and the highest yield was 36.27%±0.18%. The various properties of CNC can also be comprehensively analyzed by transmission electron microscopy, FTIR spectroscopy, XRD, thermogravimetric analysis and other studies: passion fruit peel CNC is a rod-shaped crystal with a high aspect ratio, with an average diameter of 5.12±1.63nm and an average length of 142.98±24.50nm; after multiple chemical treatments, the basic structure of cellulose remains unchanged, and the purity of cellulose is improved, and most of the impurities such as lignin and hemicellulose are removed; after chemical treatment, CNC crystals with higher crystallinity can be obtained; the optimal pyrolysis temperature of CNC is low, indicating that the thermal stability of CNC obtained after chemical treatment is reduced. In summary, passion fruit peel is a good source of cellulose and can be used as a raw material for the production of CNC. The CNC obtained after optimizing the hydrolysis conditions has a high yield and has the advantages of nanostructure, high aspect ratio, high purity, and high crystallinity, which is conducive to playing an important role in enhancing the performance of composite materials and nanomaterial modification synthesis.
[0099] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0100] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for extracting cellulose nanocrystals from passion fruit peel waste, characterized in that: The steps include: S1. Obtaining pure cellulose powder: S1.1, pre-treating the passion fruit peel without the contents to obtain passion fruit peel powder; S1.2, removing water-soluble substances from passion fruit peel powder; S1.3, remove impurities in passion fruit peel powder at one time, including lignin and hemicellulose; S1.4, removing the impurities in the passion fruit peel powder for a second time to obtain pure cellulose powder; S2. Preparation of cellulose nanocrystals: S2.1, pure cellulose powder prepared by hydrolyzing S1.4 with sulfuric acid solution; S2.2, adding condensed water to the hydrolyzate to remove the residual sulfuric acid in the pure cellulose powder after hydrolysis; S2.
3. The pure cellulose powder after hydrolysis is subjected to dialysis-centrifugation-freeze drying treatment to obtain cellulose nanocrystals.
2. A method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 1, characterized in that: In S2.1, the sulfuric acid concentration of the sulfuric acid solution is 61%, and the ratio of pure cellulose powder added is 1:20 (w / v).
3. A method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 1, characterized in that: In S2.1, the hydrolysis temperature of the sulfuric acid solution is 55°C.
4. A method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 1, characterized in that: In S2.1, the hydrolysis time is 2 h.
5. A method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 1, characterized in that: The specific steps of S1.1 are: Take the passion fruit peel with the contents removed, soak it in water, wash it, and then cut it into small pieces; Place a small piece of passion fruit peel in a 65°C oven and dry for 48 hours to obtain passion fruit dried peel; The passion fruit peel was ground into powder using a grinder and then passed through a 100-mesh sieve to obtain passion fruit peel powder.
6. A method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 5, characterized in that: The specific steps of S1.2 are: Heat the passion fruit peel powder in 80°C water at a ratio of 1:20 (w / v) to remove water-soluble substances in the passion fruit peel powder; After heating, the passion fruit peel powder is filtered and dried at 65°C.
7. A method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 6, characterized in that: The specific steps of S1.3 are: The dried fragrant fruit peel powder was mixed with 10% (w / v) sodium hydroxide solution in a ratio of 1:10 (w / v), and placed in a water bath at 80°C for 4 hours to remove impurities in the fragrant fruit peel powder at one time; The fragrant fruit peel powder is filtered and washed 4-5 times and then dried at 65°C.
8. A method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 7, characterized in that: The specific steps of S1.4 are: The fragrant fruit peel powder was mixed with 7.5% (w / v) sodium chlorite solution in a ratio of 1:10 (w / v), and placed in a water bath at 75°C for 3 hours to perform secondary impurity removal; Filter and wash the fragrant fruit peel powder to a neutral pH value, and dry it at 65°C to obtain pure cellulose powder.
9. A method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 1, characterized in that: The specific steps of S2.2 are: adding 10 times 4°C condensed water to the hydrolyzate to terminate the reaction, and centrifuging at 4°C and 1000×g for 20 min to remove residual sulfuric acid in the pure cellulose powder after hydrolysis.
10. The method for extracting cellulose nanocrystals from passion fruit peel waste according to claim 1, characterized in that: The specific steps of S2.3 are: The pure cellulose powder after hydrolysis is placed in a 6000-8000Da dialysis bag for 3 days to remove the remaining small molecular impurities in the pure cellulose powder after hydrolysis; Collect the liquid in the dialysis bag and centrifuge it again at 4°C, 1000×g for 15 min to obtain the supernatant; The supernatant was freeze-dried for 48 h to obtain cellulose nanocrystals.